2011
DOI: 10.1111/j.1574-6941.2011.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in coastal Antarctic marine microbial communities during and after melt water-related surface stratification

Abstract: Antarctic coastal waters undergo major physical alterations during summer. Increased temperatures induce sea-ice melting and glacial melt water input, leading to strong stratification of the upper water column. We investigated the composition of micro-eukaryotic and bacterial communities in Ryder Bay, Antarctic Peninsula, during and after summertime melt water stratification, applying community fingerprinting (denaturing gradient gel electrophoresis) and sequencing analysis of partial 18S and 16S rRNA genes. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
67
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 48 publications
10
67
0
2
Order By: Relevance
“…Consequently, Bacteroidetes and phytoplankton are often found in close association in polar waters (Grossart et al, 2005;Piquet et al, 2011;Williams et al, 2013) with the relative abundance of the former significantly correlated with the emergence of the late spring blooms (Alonso-Sáez et al, 2008). During May of 2014, the Flavobacteriaceae were notable by their prolific increase in relative abundance from negligible levels in March, congruent with the spike in chloroplast 16S rRNA abundance (Figure 5) and chl a maxima ( Table 1).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Consequently, Bacteroidetes and phytoplankton are often found in close association in polar waters (Grossart et al, 2005;Piquet et al, 2011;Williams et al, 2013) with the relative abundance of the former significantly correlated with the emergence of the late spring blooms (Alonso-Sáez et al, 2008). During May of 2014, the Flavobacteriaceae were notable by their prolific increase in relative abundance from negligible levels in March, congruent with the spike in chloroplast 16S rRNA abundance (Figure 5) and chl a maxima ( Table 1).…”
Section: Discussionmentioning
confidence: 57%
“…Proteorhodopsins, which support photoheterotrophic growth, have however been found in flavobacterial isolates (Gómez-Consarnau et al, 2007) previously and this may explain the peak abundance observed during the higher photoirradiance conditions of May. It has been suggested that increased numbers of Bacteroidetes would be found in the water column during spring and summer as a consequence of increased melting sea ice, either by seeding, as persistent members of sea ice biota (Bowman et al, 2012;Lo Giudice et al, 2012) or as a result of growth on organic matter released by the thawing (Piquet et al, 2011). As an abundance of Flavobacteriial proteins involved in oxidative stress protection have also been recovered from Antarctic metaproteomes, this suggests that the group may also exhibit a higher tolerance to the high solar irradiance found in polar spring and summer waters (Williams et al, 2013) and may indeed come to play a more dominant role in the surface layers of an ice-free Arctic.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, here we hypothesize that heterotrophic dinoflagellates, which represent a large part of Antarctic microzooplankton biomass, can be responsible for significant losses of daily primary production. The results of Price and Steinberg (2013) suggest that microzooplankton may usually control the start of blooms in areas like coastal KGI, when Chl a values are low (i.e., , 0.5 mg m 23 ; Sherr and Sherr 2009) and substantially contribute to their decay (Calbet and Landry 2004). However, phytoplankton blooms are normal features in many other coastal Antarctic areas, and this can be attributed to the generally low growth rates of heterotrophic protists in cold waters, compared with phytoplankton (Rose and Caron 2007), resulting in uncoupled grazing activity of microzooplankton regarding phytoplankton growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…Significant interannual climate variability in sea ice extension and ocean surface temperatures along the WAP has been associated with the Southern Annular Mode (SAM) and the El Niñ o Southern Oscillation (ENSO; Meredith et al 2008;Schloss et al 2012). Climate warming is supposed to induce important changes in polar ecosystems, from microbial communities (Piquet et al 2011) to apex predators' levels (Trathan et al 2007). Phytoplankton is at the base of the food web so that changes affecting primary production dynamics affect organisms of higher trophic levels.…”
mentioning
confidence: 99%
“…2) showing a homogeneous water column for the upper 60 m at the O and M stations. The resultant vertical redistribution of phytoplankton biomass may have interrupted bloom formation, and could cause changes in phytoplankton composition, as found before (Piquet et al, 2011;Hegseth and Tverberg, 2013). After the wind event, a period characterized by relatively calm southerly winds permitted stabilization of the water column and therefore biomass buildup.…”
Section: Kongsfjorden Springtime Phytoplankton Dynamicsmentioning
confidence: 99%